2017
DOI: 10.2215/cjn.09270816
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and CKD in Chinese Adults: A Cross-Sectional Study

Abstract: Worse overall sleep quality was associated with higher odds of being high or very high risk for CKD and proteinuria in Chinese adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 40 publications
0
62
1
Order By: Relevance
“…As part of the Chronic Renal Insufficiency Cohort (CRIC) study, Knutson et al reported worse objective sleep quality was associated with a lower estimated GFR (eGFR) and higher urinary protein to creatinine ratio [170]. In addition, a shorter duration of sleep and later timing of sleep was associated with a lower eGFR Similar studies involving participants from the Chinese Kailuan cohort [171] and Korean Kangbuk Samsung Health Study [172] also found an association between poor sleep quality and reduced renal function. Given that sleep disturbances are a common problem in dialysis patients [173], and that disturbances in circadian timekeeping have been observed in the peripheral tissues of patients on dialysis as well [174], these studies suggest a possible dyssynchrony between central and peripheral clocks in the body and require further analysis of the circadian clock mechanism in CKD patients to reveal new clinical avenues to treat the disease and its symptoms.…”
Section: Pathologies Associated With Impaired Circadian Rhythmsmentioning
confidence: 99%
“…As part of the Chronic Renal Insufficiency Cohort (CRIC) study, Knutson et al reported worse objective sleep quality was associated with a lower estimated GFR (eGFR) and higher urinary protein to creatinine ratio [170]. In addition, a shorter duration of sleep and later timing of sleep was associated with a lower eGFR Similar studies involving participants from the Chinese Kailuan cohort [171] and Korean Kangbuk Samsung Health Study [172] also found an association between poor sleep quality and reduced renal function. Given that sleep disturbances are a common problem in dialysis patients [173], and that disturbances in circadian timekeeping have been observed in the peripheral tissues of patients on dialysis as well [174], these studies suggest a possible dyssynchrony between central and peripheral clocks in the body and require further analysis of the circadian clock mechanism in CKD patients to reveal new clinical avenues to treat the disease and its symptoms.…”
Section: Pathologies Associated With Impaired Circadian Rhythmsmentioning
confidence: 99%
“…Interventional trials to suppress deep nonrapid eye movement sleep, also known as slow-wave sleep, demonstrated adverse metabolic effects on glucose metabolism (24,25), the sympathetic nervous system (25), and adrenocortical activity (25). Although poor sleep quality is common in patients with CKD (26)(27)(28), the clinical effect of sleep quality on ESKD incidence remains to be elucidated (19).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, previous studies have demonstrated that SA is an independent risk factor for CKD in both direct and indirect effects . SA can accelerate the deterioration of kidney function directly by activating renin‐angiotensin‐aldosterone system, sympathetic nervous system and nocturnal hypoxia . Meanwhile, SA can promote the decline of renal function indirectly by contributing to risk factors for CKD, such as, obesity and diabetes .…”
Section: Discussionmentioning
confidence: 99%